Developing precipitation modes for preventing the calcium-oxalate contamination of sugar beet pectins. (1st September 2015) - Guo, Xiaoming; Meng, Hecheng; Zhu, Siming; Tang, Qiang; Pan, Runquan; Yu, Shujuan
Highlights: Calcium oxalates particles were formed during ethanol precipitation. SBP was contaminated by the formed calcium-oxalates particles. Precipitation modes influenced the occurrence of calcium-oxalate contamination. Effects of precipitation modes on emulsifying properties of SBP were studied. Abstract: Effects of precipitation modes on the co-precipitation of insoluble oxalates particles during the purification of sugar beet pectins (SBP) from the extract were investigated. It was observed that soluble oxalate ions formed insoluble oxalate salts with calcium and precipitated with pectins during ethanol precipitation as pH of the medium increased and the solvent changed from water to ethanol–water mixture. Comparison among the employed precipitation methods revealed that both the dialysis–ethanol-precipitation and metal precipitation effectively prevented the calcium-oxalate contamination of SBP. Emulsifying properties of DEPP, EPP and MPP were also studied. It was observed that DEPP performed better than the remainder with respect to emulsifying ability. Based on these results, we concluded that the dialysis–ethanolic-precipitation can be a suitable method for improving the purity as well as emulsifying properties of the resulting pectins.